2018
DOI: 10.1016/j.resuscitation.2018.01.040
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and outcome of paediatric out-of-hospital cardiac arrests: A paediatric sub-study of the Pan-Asian resuscitation outcomes study (PAROS)

Abstract: The wide variation in the survival outcomes amongst the seven countries in our study may be due to the differences in the delivery of pre-hospital interventions and bystander CPR rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 26 publications
(51 reference statements)
0
57
1
Order By: Relevance
“…There were signi cant between-group differences in the rates of intubation and de brillation. Furthermore, signi cantly fewer adrenaline doses were administered in the ROSC than in the no ROSC group (4 [2-6] vs 6 [3][4][5][6][7][8][9][10], p <0.05). Table 4 shows the timeline of resuscitative activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were signi cant between-group differences in the rates of intubation and de brillation. Furthermore, signi cantly fewer adrenaline doses were administered in the ROSC than in the no ROSC group (4 [2-6] vs 6 [3][4][5][6][7][8][9][10], p <0.05). Table 4 shows the timeline of resuscitative activity.…”
Section: Resultsmentioning
confidence: 99%
“…Out-of-hospital cardiac arrest (OHCA) is very rare in the paediatric population, with an annual incidence of 2-9 cases per 1,000,000 children (1)(2)(3)(4)(5). There are several guidelines on paediatric cardiac arrest, such as the Pediatric Advanced Life Support issued by the American Heart Association: however, the outcome of OHCA in paediatric patients is very poor, with survival rates ranging from 2% to 22% (1)(2)(3)(4)(5)(6). In a recent literature review of the science of paediatric resuscitation, Topjian et al reported that 5-10% of paediatric OHCA victims survive to hospital discharge, and only 0-12% of those have a good neurological outcome (7).…”
Section: Introductionmentioning
confidence: 99%
“…The evidence comparing TI with SGA during pediatric resuscitation comes from 4 observational studies of OHCA 111À113,120 ; 2 of these studies used propensity matching. 111,112 When combined, neither the propensity-matched studies 111,112 nor the unadjusted cohort studies 113,120 found a significant association between the choice of advanced airway and survival with favorable neurological function or survival to hospital discharge.…”
Section: Consensus On Sciencementioning
confidence: 93%
“…111,112 Two other observational studies reported only unadjusted data. 113,120 None of these studies found a significant association between SGA use and survival with favorable neurological function or survival to hospital discharge.…”
Section: Consensus On Sciencementioning
confidence: 99%
“…No bAED use was reported for any POHCA case in the region. Two studies reported ROSC, 5.9% (31) and 14% (29). Two studies reported a survival to discharge rate of approximately 6% (13,31).…”
Section: Process and Outcome Characteristicsmentioning
confidence: 99%